2017
DOI: 10.1007/s00192-017-3303-x
|View full text |Cite
|
Sign up to set email alerts
|

Architectural assessment of rhesus macaque pelvic floor muscles: comparison for use as a human model

Abstract: Introduction and hypothesis Animal models are essential to further our understanding of the independent and combined function of human pelvic floor muscles (PFMs), as direct studies in women are limited. To assure suitability of the rhesus macaque (RM), we compared RM and human PFM architecture, the strongest predictor of muscle function. We hypothesized that relative to other models, RM best resembles human PFM. Methods Major architectural parameters of cadaveric human coccygeus, iliococcygeus, and pubovisc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…Studies utilizing a rabbit model indicate that, similar to the muscles described above, the EAS operates at L s < optimal L s [8]. However, rabbit models have not been validated for human EAS and it has previously been shown that rabbit pelvic floor muscles’ architecture is the least similar to humans among experimental animals commonly used for pelvic floor disorder research [14, 15]. The same investigators used imaging combined with anal manometry to demonstrate that EAS contractile force rises with increasing distension in human clinical studies [16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies utilizing a rabbit model indicate that, similar to the muscles described above, the EAS operates at L s < optimal L s [8]. However, rabbit models have not been validated for human EAS and it has previously been shown that rabbit pelvic floor muscles’ architecture is the least similar to humans among experimental animals commonly used for pelvic floor disorder research [14, 15]. The same investigators used imaging combined with anal manometry to demonstrate that EAS contractile force rises with increasing distension in human clinical studies [16].…”
Section: Introductionmentioning
confidence: 99%
“…For example, indirect clinical assessments led to the notion that the human puborectalis muscle operates at a short L s [17]. In contrast, our previous direct tissue level assessments of the human pelvic floor muscles demonstrate that the puborectalis operates at optimal L s [15]. Furthermore, direct anatomical studies enable the assessment of the individual components of the anal sphincter complex, providing a critical advantage over the indirect techniques that simultaneously measure the output of the entire complex.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, architectural studies of the female pelvic floor muscles showed that rats, compared to other commonly used laboratory animals, such as rabbit and mouse, were the closest to humans in terms of muscle design (Alperin et al, 2014). Moreover, the architectural difference index of rat pelvic floor muscles, which quantifies how closely rat muscle architecture resembles human muscle architecture, was comparable to the architectural difference index of the non-human primate (Brown et al, 2010;Lieber and Brown, 1992;Stewart et al, 2017).…”
Section: Introductionmentioning
confidence: 95%
“…; Stewart et al. ). Furthermore, using this model, we have discovered the existence of protective pregnancy‐induced adaptations in these muscles (Alperin et al.…”
Section: Introductionmentioning
confidence: 98%
“…The rat is the most widely used experimental model in pelvic floor disorders research. Through a comparative analysis of the human and rat PFM architecture, the main determinant of in vivo muscle function, we have previously validated the rat model with respect to PFMs (Alperin et al 2014;Stewart et al 2017). Furthermore, using this model, we have discovered the existence of protective pregnancy-induced adaptations in these muscles (Alperin et al 2015(Alperin et al , 2016.…”
Section: Introductionmentioning
confidence: 99%